2019
DOI: 10.1016/j.ebiom.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identifies brain acid soluble protein 1 (BASP1) as a prognostic biomarker candidate in pancreatic cancer tissue

Abstract: Background: Pancreatic cancer is a heterogenous disease with a poor prognosis. This study aimed to discover and validate prognostic tissue biomarkers in pancreatic cancer using a mass spectrometry (MS) based proteomics approach. Methods: Global protein sequencing of fresh frozen pancreatic cancer and healthy pancreas tissue samples was conducted by MS to discover potential protein biomarkers. Selected candidate proteins were further verified by targeted proteomics using parallel reaction monitoring (PRM). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…The BASP1 gene is downregulated in most mammalian cancers, and tumor‐suppressive functions of BASP1 were observed in several human cancer models (Guo et al , ; Marsh et al , ; Zhang et al , ; Zhou et al , ; Zhou et al , ). This corroborates our original finding that BASP1 strongly interferes with v‐Myc‐induced oncogenicity and displays properties of a tumor suppressor (Hartl et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BASP1 gene is downregulated in most mammalian cancers, and tumor‐suppressive functions of BASP1 were observed in several human cancer models (Guo et al , ; Marsh et al , ; Zhang et al , ; Zhou et al , ; Zhou et al , ). This corroborates our original finding that BASP1 strongly interferes with v‐Myc‐induced oncogenicity and displays properties of a tumor suppressor (Hartl et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the WT1 targets is MYC , which is activated by WT1 but suppressed by a WT1 : BASP1 complex (Goodfellow et al , ; Green et al , ; Han et al , ; Wu et al , ). Recent studies showed that WT1 is activated in pancreatic cancer and that patients with elevated BASP1 levels have a significantly better prognosis than individuals whose cancer cells contain no BASP1 but high WT1 levels (Zhou et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Sample processing and LC-MS/MS analysis were performed as reported previously [10]. Briefly, proteins extracted from fresh frozen pancreas specimens were reduced, alkylated and digested into peptides using Lys-C and trypsin.…”
Section: Ms-based Proteomicsmentioning
confidence: 99%
“…Proteomics is a valuable complement to genetic studies. Mass spectrometry (MS)-based proteomics profiling of patient-derived samples has been suggested as an effective approach for the discovery of biomarkers and detection of suitable therapeutic targets in many cancers [7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation